A New Flap Alternative for Trochanteric Pressure Sore Coverage: Distal Gluteus Maximus Musculocutaneous Advancement Flap. Issue 2 (February 2015) - Nisanci, Mustafa; Sahin, Ismail; Eski, Muhitdin; Alhan, Dogan
Abstract : Abstract: Management of long-term bedridden patients experiencing pressure sores still represents a surgical challenge due to limited flap alternatives and high recurrence rates after the treatment. Fasciocutaneous, musculocutaneous, local perforator-based flaps, and free flaps have all been used for treatment of trochanteric pressure sores. This study presents a new use of distal gluteus maximus (GM) muscle as an advancement musculocutaneous flap for coverage of trochanteric pressure sores in 7 patients. The technique involves design of a long V-shaped skin island over the distal fibers of the GM muscle, beginning from the inferoposterior wound edge and extending inferomedially, almost parallel to the gluteal crease. After its harvest as an island flap on the distal fibers of the GM muscle, the skin paddle can be advanced onto the trochanteric defect, whereas the muscle itself is rotated after severing its insertion to femur. If a second triangular skin island is designed on the proximal fibers of GM muscle to cover an associated sacral defect, 2 coexisting pressure sores can be reconstructed concomitantly with 2 skin paddles on a single muscle belly at 1 surgical setting. Of the 7 patients, 3 had 3 (bilateral trochanteric and sacral), 2 had 2 (sacral and trochanteric), and 2 had 1 (only trochanteric) pressure sores. All ulcers were closed successfully and all of the flaps survived totally without any complication except the one in which we experienced minimal wound dehiscence in the early postoperative period. Conclusively, our current surgical method provided a reliable coverage for trochanteric pressure sores although it was technically straightforward and fast. Additionally, it offers simultaneous closure of 2 pressure ulcers with 2 skin islands on a single muscle flap.